Rapid decline in insulin antibodies and glutamic acid decarboxylase autoantibodies with ibrutinib therapy of chronic lymphocytic leukaemia. (28th July 2017) - Skrabs, C.; Pickl, W. F.; Perkmann, T.; Jäger, U.; Gessl, A.
Summary: What is known and objective: Ibrutinib is inhibiting the Bruton's tyrosine kinase (BTK), thereby influencing B‐cell development. We describe an unexpected side effect of ibrutinib in two patients with chronic lymphocytic leukaemia concerning the vigorous decrease of two different diabetes‐associated antibodies. Case description: Two weeks after onset of ibrutinib therapy, patient A frequently noticed symptoms of hypoglycaemia such as dizziness and blurred vision. Blood glucose declined to 35‐40 mg/dL. He had to lower his insulin dose step by step. High levels of insulin antibodies which had developed during insulin therapy were detected. Seven weeks after start of ibrutinib, his insulin antibodies level had dropped by 54.6%. Patient B had a 54.1% decrease in his glutamic acid decarboxylase autoantibodies level after 7 weeks. What is new and Conclusion: The inhibitory effect of ibrutinib on the levels of insulin antibodies and glutamic acid decarboxylase autoantibodies is a novel finding and may have implications for diabetes care. Abstract : Two patients with CLL and diabetes mellitus experienced a remarkable side effect to ibrutinib. While patient A's chronic lymphocytic leukaemia was responding gradually to the drug, he was showing a simultaneous reduction in level of insulin antibodies which had developed during insulin therapy for type 2 diabetes. In patient B, we detected a substantial decline in glutamic acid decarboxylase autoantibodies (marker of type 1 diabetes and latent autoimmune diabetes in adults).